2020
DOI: 10.1093/nar/gkaa092
|View full text |Cite
|
Sign up to set email alerts
|

RNase II binds to RNase E and modulates its endoribonucleolytic activity in the cyanobacterium Anabaena PCC 7120

Abstract: In Escherichia coli, the endoribonuclease E (RNase E) can recruit several other ribonucleases and regulatory proteins via its noncatalytic domain to form an RNA degradosome that controls cellular RNA turnover. Similar RNA degradation complexes have been found in other bacteria; however, their compositions are varied among different bacterial species. In cyanobacteria, only the exoribonuclease PNPase was shown to bind to the noncatalytic domain of RNase E. Here, we showed that Alr1240, a member of the RNB famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…Notably, protein-protein interaction sites with DEAD-box helicase CrhB and RNase II were mapped to the N-terminal, catalytic domain of RNase E of the cyanobacterium Anabaena (Nostoc) sp. PCC 7120 (77, 78). In E. coli , the analogous binding site of helicase RhlB is located within the C-terminal domain (31).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, protein-protein interaction sites with DEAD-box helicase CrhB and RNase II were mapped to the N-terminal, catalytic domain of RNase E of the cyanobacterium Anabaena (Nostoc) sp. PCC 7120 (77, 78). In E. coli , the analogous binding site of helicase RhlB is located within the C-terminal domain (31).…”
Section: Discussionmentioning
confidence: 99%
“…RebA does not contain any domains or motifs that may confer the activities for RNA cleavage or binding, consistent with our results tested with synthetic RNAs in the presence of RebA (Figures 2A, 2B and S2A). However, with 5' p-LU13-FAM, a 13-nt oligoribonucleotide with a 5'-monophosphate and a 3' FAM modification that has been used as an RNase E substrate previously (Zhou et al, 2020), we found that RebA when present at more than 2-fold molar excess could strongly interfere with the substrate binding activity of RNase E (Figure 2C), suggesting that it may function as a regulator of the RNase E activity. We thus further tested the RNase E activity in the presence of RebA.…”
Section: Reba Inhibits the Binding And The Cleavage Activities Of Rna...mentioning
confidence: 75%
“…pKT25a and pUT18Ca have identical cloning site, thus allowing the same fragment to be cloned into both vectors. All the two hybrid plasmids were constructed by seamlessly cloning as previously described (Zhou et al, 2020).…”
Section: Construction Of Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study shows that an RNase II/R protein (identified here as Zam) from Anabaena sp. PCC 7120 interacts with and enhances the activity of RNase E, the major degradosome enzyme, via its cold-shock and S1 domains [ 47 ]. This finding prompts us to propose a different model in which Zam binding to RNase E under oxidizing, but not reducing, conditions increases RNA turnover rates.…”
Section: Discussionmentioning
confidence: 99%